HABITUASI PESERTA DIDIK MELALUI PROGRAM WALI ASUH DALAM MEMBENTUK KARAKTER SANTRI DI PONDOK PESANTREN - Masyitoh - (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
This paper presents the habituation of students through the guardian program for enhancing santri character in pesantren Nurul Jadid Paiton Probolinggo. Caregivers have an important role in nurturing and giving guidance and directing to have superior, by instilling a habit of good character towards santri consistently and continuously. This study uses a qualitative approach type case study. The results showed that; habituation of santri through foster care programs is carried out through; 1) Enforcement through the activation of the disciplinary character of the santri with no violence, 2) indoctrinization of values expressly and continuously, 3) mauidhoh hasanah which is done continuously, 4) modeling / uswatun hasanah, 5) personal approach to strengthen the soul and physical santri, and 6) assistance through intensive supervision in santri activities. The character built from habituation is, the trilogy of santri, which includes; pay attention to the obligations of fardu ain, introspective by leaving great sins, be virtuous to Allah and the Creator, and the five consciousnesses of the santri, namely; religious awareness, knowledge, organization, community and nation and state.